A Promising Single Oral Disintegrating Tablet for Co-Delivery of Pitavastatin Calcium and Lornoxicam Using Co-Processed Excipients: Formulation, Characterization and Pharmacokinetic Study - Teaima MH; Abdel-Haleem KM; Osama R; El-Nabarawi MA; Elnahas OS (Dove Medical Press, 2021)
Mahmoud H Teaima,1 Khaled M Abdel-Haleem,2 Rewan Osama,2 Mohamed A El-Nabarawi,1 Osama S Elnahas2 1Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Cairo University, Cairo, Egypt; 2Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, October 6 University, Giza, EgyptCorrespondence: Mahmoud H TeaimaDepartment of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Cairo University, Kasr El-Aini Street, Cairo, 11562, EgyptTel +201005840264Email mahmoud.teaima@pharma.cu.edu.egSignificance: Statins are an important class of drugs that help to control hyperlipidemia, and one of these statins recently used is pitavastatin calcium (PITA). Nevertheless, the most reported adverse effect of statins is myopathy. Therefore, combining statins with non-steroidal anti-inflammatory drugs (NSAIDs) as Lornoxicam (LORNO) can help in the management of statin-induced myopathy.Purpose: This study aimed to formulate and evaluate different oral disintegrating tablets (ODTs) containing PITA using different co-processed excipients. The best PITA-ODT was selected and reformulated with the addition of LORNO, forming a single ODT comprising both drugs. The pharmacokinetic parameters of PITA and LORNO in a single ODT were compared to those of the marketed products (Lipidalon® and Lornoxicam®).Methods: Eight PITA-ODTs were prepared via direct compression. The prepared PITA-ODTs were evaluated for their weight variation, thickness, breaking force, friability, drug content, and wetting time (WT). In-vitro disintegration time (DT) and dissolution were also evaluated and taken as parameters for selection of the best formula based on the criteria of scoring the fastest DT and highest Q10 min. LORNO was added to the selected PITA-ODT, forming a single ODT (M1) comprising both drugs, which was subjected to an in-vivo pharmacokinetic study using rats as an animal model and liquid chromatography-mass spectrometry (LC-MS/MS) for analysis of both drugs in rat plasma.Results: Results showed that all PITA-ODTs had acceptable physical properties in accordance with pharmacospecial standards. PITA-ODT prepared with Pharmaburst® (F2) had significantly (p< 0.05) the fastest DT (6.66± 1.52 s) and highest Q10 min (79.07± 2.02%) and was chosen as the best formula. The in-vivo pharmacokinetic study of M1 formula showed higher percent relative bioavailability (%RB) of 286.7% and 169.73% for PITA and LORNO, respectively, compared with the marketed products.Conclusion: The single ODT comprising PITA and LORNO was promising for instant co-delivery of both drugs with higher %RB when compared with the marketed products.Keywords: oral disintegrating tablets, co-processed excipients, pitavastatin calcium, Lornoxicam, in-vivo pharmacokinetic study, liquid chromatography-mass spectrometry